Elucidating the high compliance mechanism by which the urinary bladder fills under low pressures - Fatemeh Azari; Anne M. Robertson; Yasutaka Tobe; Paul N. Watton; Lori A. Birder; Naoki Yoshimura; Kanako Matsuoka; Christopher Hardin; Simon Watkins (Scientific Reports)
Abstract The high compliance of the urinary bladder during filling is essential for its proper function, enabling it to accommodate significant volumetric increases with minimal rise in transmural pressure. This study aimed to elucidate the physical mechanisms underlying this phenomenon by analyzing the ex vivo filling process in rat from a fully voided state to complete distension, without preconditioning, using three complementary imaging modalities. High-resolution micro-CT at 10.8 $$\upmu$$ m resolution was used to generate detailed 3D reconstructions of the bladder lumen, revealing an average 62-fold increase in bladder volume during filling. Pressure-volume studies of whole bladder delineated three mechanical filling regimes: an initial high-compliance phase, a transitional phase, and a final high-pressure phase. While prior studies conjectured small mucosal rugae ( $$\sim$$ 450 $$\upmu$$ m) are responsible for the high compliance phase, multiphoton microscopy (MPM) of the dome of the voided bladder revealed large folds in voided bladders an order of magnitude larger than these rugae. Bladder imaging during the inflation process demonstrated flattening of these large scale folds in the initial high compliance phase. The 3D reconstructions of the bladder lumen in the filled and voided state revealed a high voiding efficiency of 97.13% ± 2.42%. The MPM imaging results suggest the large scale folds in the dome enable this high voiding fraction by driving urine toward the bladder outlet. These insights are vital for developing realistic computational models of bladder micturition and understanding changes to bladder function due to pathological conditions such as bladder outlet obstruction and age-related dysfunction.